PENGARUH IKLIM ORGANIASASI DAN MOTIVASI TERHADAP KINERJA DOSEN DI SEKOLAH TINGGI ILMU EKONOMI NAHDLATUL ULAMA (STIENU) JEPARA - Eko Nur Fu'ad (Sains Manajemen, 2015)
In order to optimize the performance of the lecturer at the Faculty of Economics and Business (FEB), University of Islamic Nahdlatul Ulama (UNISNU) Jepara need to find theright model. The authors analyze the influence of independent variables include:organizational climate , work motivation and job satisfaction on the performance of the lecturer. The survey was conducted on fifty-five lecturers in the STIENU Jepara. The results showed the influence of organizational climate, work motivation and the job satisfaction to performance of the lecture